Interactive effects of mechanical stress, sand burial and defoliation on growth and mechanical properties in Cynanchum komarovii. (7th June 2012) - Xu, L.; Yu, F.‐H.; Werger, M.; Dong, M.; Anten, N. P. R.
Abstract: In drylands, wind, sand burial and grazing are three important factors affecting growth and mechanical properties of plants, but their interactive effects have not yet been investigated. Plants of the semi‐shrub Cynanchum komarovii, common in semi‐arid parts of NE Asia, were subjected to brushing, burial and defoliation. We measured biomass allocation and relative increment rates of dry mass (RGRm ), height (RGRh ) and basal diameter (RGRd ). We also measured the stem mechanical properties, Young's modulus ( E ), second moment of area ( I ), flexural stiffness ( EI ) and breaking stress ( σ b ), and scaled these traits to the whole‐plant level to determine the maximum lateral force ( F lateral ) and the buckling safety factor (BSF). Brushing increased RGRm ; neither burial nor defoliation independently affected RGRm, but together they reduced it. Among buried plants, brushing positively affected stem rigidity and strength through increasing RGRd, E, I and EI, and at whole plant level this resulted in a larger BSF and F lateral . However, among unburied plants this pattern was not observed. Our results thus show that effects of mechanical stress and grazing on plants can be strongly modified by burial, and these interactions should be taken into account when considering adaptive significance of plant mechanical traits in drylands.